Development of the Partial Discharges Inception Voltage for Different Sets of Pre-Aged PILC Cable Samples - Mladenovic, Ivana; Weindl, Christian (ISEI 2010, 2010)
Diagnostics and the rest life time estimation of the electrical equipment play an important role in the power network investment and maintenance planning. In order to develop a reliable correlation between the partial discharges and the time to the next failure of the MV PILC cables, a special system called ICAAS (Integrated Cable Accelerated Aging System) for the artificial accelerated aging was developed. The aging system includes highly sensitive and selective PD-detection and tan(δ)-measurement units. During the entire aging process, a knowledge data-base will be formed up, by the constant monitoring of all relevant aging parameters and measured values. The functionality of the ICAAS was confirmed in a pre-test and the most suitable ageing and physical parameters for the main aging experiment, which should last for two years in continuity, were determined. Therefore two different sets of cable samples were used in the pre-test. Group one was made up of samples of brand new cables, in a second group nine 20 years old cables were aged, including cables with an existing and defined partial discharge level. In this paper the results, by meaning of partial discharge activities and environmental influence of the pre-test will be shown and discussed. The physical processes that appear in the cable insulation of PILC cables will be discussed, and in this way the limitations in the electrical aging parameters. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.develo_8
Keywords: Artificial aging; Diagnosis; Inception voltage; MV cable; Partial discharge; Rest life time